Neurociência e direito penal: a culpabilidade e o panorama das implicações neurocientíficas - Ferracioli, Jéssica Cristina (2018)
This thesis aims to outline the main aspects that involve Neuroscience and Guilt in the sphere of Criminal Law, under the aegis of the conclusions of the current neuroscientific experiments, as well as to outline their implications for Criminal Law. It is known that, at present, Neuroscience has uncovered aspects that involve human behavior, drawing on various existing methods and techniques, as well as providing new elements on brain functioning, with unprecedented advances throughout human history. As a result of the current stage of neuroscientific findings, questions have arisen about possible culpability impacts and, furthermore, the search for the making of a compatible criterion among the disciplines involved has grown, especially for the purpose of excluding or adjudicating criminal responsibility due to a cerebral dysfunction that might be responsible for the agent’s behavioral change and that may have led to the criminal act. The subject of study is approached through a bibliographical research, given that, in view of the interdisciplinary provocation that it involves, it is intended to draw a general panorama of the discussion under a compatibility approach. The questions raised by the neuroscientific studies and that may impact in the future penal dogmatism, the model of judicial decisions and the attribution of criminal responsibility corroborate the relevance of this study